A Chrnb3‐Cre BAC transgenic mouse line for manipulation of gene expression in retinal ganglion cells. Issue 9 (14th May 2019) - Drayson, Lucy E.; Triplett, Jason W.
Summary: The mechanisms by which retinal ganglion cells (RGCs) make specific connections during development is an intense area of research and have served as a model for understanding the general principles of circuit wiring. As such, genetic tools allowing for specific recombination in RGCs are critical to further our understanding of the cell‐specific roles of different genes during these processes. However, many RGC‐specific Cre lines have drawbacks, due to their broad expression in other cell types and/or retinorecipient regions or lack of expression in broad swaths of the retina. Here, we characterize a Cre BAC transgenic line driven by elements of the cholinergic receptor nicotinic beta 3 subunit (Chrnb3). We show that Cre expression is restricted to RGCs in the retina and sparsely expressed in the brain, importantly excluding retinorecipient regions. Furthermore, Chrnb3‐Cre mice label a wide variety of RGCs distributed throughout the retina and Cre activity is detected embryonically, shortly following RGC differentiation. Finally, we find that Chrnb3‐Cre‐labeled RGCs innervate multiple retinorecipient areas that serve both image‐forming and nonimage forming functions. Thus, this genetic tool will be of broad use to investigators studying the RGC‐specific contributions of genes to visual circuit development.